Providing Measurement, Evaluation, Accountability, and Leadership Support (MEALS) for Non-communicable Diseases Prevention in Ghana: Project Implementation Protocol - Laar, Amos; Kelly, Bridget; Holdsworth, Michelle; Quarpong, Wilhemina; Aryeetey, Richmond; Amevinya, Gideon Senyo; Tandoh, Akua; Agyemang, Charles; Zotor, Francis; Laar, Matilda E.; Mensah, Kobby; Laryea, Dennis; et al. (Frontiers in Nutrition, 2021)
Background This paper describes the rationale, adaptation and final protocol of a project developed to address the increase in obesity and nutrition-related non-communicable diseases (NR-NCDs) in Ghana. Code-named Measurement, Evaluation, Accountability, and Leadership Support for NCDs (MEALS4NCDs) project, it aims to measure and support public sector actions that create healthy food marketing, retail and provisioning environments for Ghanaian children, using adapted methods from the International Network for Food and Obesity/NCDs Research Monitoring and Action Support (INFORMAS). Methods The protocol for this observational study draws substantially from the INFORMAS’ Food Promotion and Food Provision Modules. However, to appraise the readiness of local communities to implement interventions with strong potential to improve Ghanaian children’s food environments, the MEALS4NCDs protocol has innovatively integrated a local community participatory approach based on the Community Readiness Model (CRM) into the INFORMAS approaches. The setting is Ghana, and the participants include health and nutrition policy makers, nutrition, and food service providers, consumers, school authorities, and pupils of Ghanaian basic schools. Results The study establishes a standardised approach to providing implementation science evidence for NCDs prevention in Ghana. It demonstrates feasibility and innovative application of the INFORMAS expanded Food promotion and Food provision modules, together with the integration of the CRM in a lower-middle income setting. Conclusion The research will facilitate understanding of the processes through which the INFORMAS approach is contextualized to a lower-middle income African context. The protocol could be adapted for similar country settings to monitor relevant aspects of children’s food environments.